Pervasiveness of the IQ Rise: A Cross-Temporal Meta-Analysis - Pietschnig, Jakob; Voracek, Martin; Formann, Anton K. (PloS one, 2010)
Generational IQ gains in the general population (termed the Flynn effect) show an erratic pattern across different nations as well as across different domains of intelligence (fluid vs crystallized). Gains of fluid intelligence in different countries have been subject to extensive research, but less attention was directed towards gains of crystallized intelligence, probably due to evidence from the Anglo-American sphere suggesting only slight gains on this measure. In the present study, development of crystallized intelligence in the German speaking general population is assessed. To investigate whether IQ gains for crystallized intelligence are in progress in German-speaking countries, two independent meta-analyses were performed. By means of a cited reference search in ISI Web of Science, all studies citing test manuals and review articles of two widely-used salient measures of crystallized intelligence were obtained. Additionally, the electronic database for German academic theses was searched to identify unpublished studies employing these tests. All studies reporting participants mean IQ or raw scores of at least one of the two measures were included in the present analyses, yielding over 500 studies (>1,000 samples; >45,000 individuals). We found a significant positive association between years of test performance and intelligence (1971-2007) amounting to about 3.5 IQ points per decade. This study clearly demonstrates that crystallized IQ gains are substantial and of comparable strength as Flynn effects typically observed for measures of fluid intelligence in Central Europe. Since mean IQ was assessed in a large number of small, non-representative samples, our evidence suggests a remarkable robustness of these gains. Moreover, in both meta-analyses strength of gains was virtually identical. On the whole, results of the present study demonstrate a pervasive and generalizing Flynn effect in German-speaking countries.